NGHIÊN CỨU CHẾ TẠO VẬT LIỆU XÚC TÁC QUANG HÓA TiO2/GO ỨNG DỤNG XỬ LÝ PHẨM MÀU DB71 TRONG MÔI TRƯỜNG NƯỚC - Nguyễn, Mạnh Tường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SYNTHESIZING PHOTOCATALYTIC MATERIAL TiO2/GO USED FOR DIRECTLY DEGRADING BLUE 71 (DB71) IN AQUEOUS SOLUTIONIn this paper a new photocatalytic material based on graphenoxit and titan dioxide was studied. GO was synthesized by Tour method. Titanium dioxide catalyst carried on graphenoxit was successfully synthesized using the sol-gel method. The photocatalytic activity of GO/TiO2 on degrading DB71 in depending on pH and GO:TiO2 mass ratio were investigated. With a concentration of DB71 of 20 ppm, pH = 4 and after 30 minutes of reaction, the treatment efficiency of the TiO2/GO with mass ratio of 1,5:1 was 100%. This result demonstrates that GO doped TiO2 has high photocatalytic activity.